Preparation of a low contact angle water-based coating using ultrasonic irradiation. Issue 6 (28th October 2014) - Zhang, X.R.; Liu, L.Z.; Li, J.F.; Cui, W.W.; Weng, L.
Abstract : Purpose: – The key purpose of this study was to investigate the effects of different ultrasonic irradiation times on the wettability and other properties of the resulting water-based coating. The subject water-based coating was prepared using water-soluble polyester and amino resins by ultrasonic oscillation. Design/methodology/approach: – The coating was prepared by polymerising polyester and amino resins in water using ultrasonic oscillation. The coating was baked for 40 seconds at 350°C to coalesce and solidify the film. The contact angle, thermal stability and mechanical properties of the film, as well as the molecular weight (MW) and structure of the polyester resin, were determined. Findings: – The contact angle of the coating was found to decrease with ultrasonic irradiation; the mechanical properties and thermal stability were not altered when the irradiation time was longer than 5 hours. The MW of the polyester initially decreased then increased and stabilized with ultrasonic irradiation. The structure of polyester molecule and aggregated state of the solidified coating were not changed by ultrasonic irradiation. Research limitations/implications: – In the study reported here, the effects of different ultrasonic irradiation times were investigated. Results of this research could benefit in-depth understanding of the influence of ultrasonic treatment on polyester resins and polyester coatings and could further promote the development of water-based coatings. Originality/value: – The contact angle of the water-based coating decreased by mechanical means. The effects of ultrasound on microstructure and properties of the coating and resin were discussed in detail.